An effective approach to quantitative analysis of ternary amino acids in foxtail millet substrate based on terahertz spectroscopy. (25th April 2018) - Lu, Shao Hua; Li, Bao Qiong; Zhai, Hong Lin; Zhang, Xin; Zhang, Zhuo Yong
Highlights: Tchebichef moment (TM) method was proposed to the analysis of THz spectra. TM method could eliminate the serious interferences without any pretreatment. TM method was applied on the analysis of the three amino acids in actual substrate. Compared with others, our method have more accuracy and reliability. Our study provided a potential method to quantify multicomponent with THz-TDS. Abstract: Terahertz time-domain spectroscopy has been applied to many fields, however, it still encounters drawbacks in multicomponent mixtures analysis due to serious spectral overlapping. Here, an effective approach to quantitative analysis was proposed, and applied on the determination of the ternary amino acids in foxtail millet substrate. Utilizing three parameters derived from the THz-TDS, the images were constructed and the Tchebichef image moments were used to extract the information of target components. Then the quantitative models were obtained by stepwise regression. The correlation coefficients of leave-one-out cross-validation ( R loo - cv 2 ) were more than 0.9595. As for external test set, the predictive correlation coefficients ( R p 2 ) were more than 0.8026 and the root mean square error of prediction ( RMSEp ) were less than 1.2601. Compared with the traditional methods (PLS and N -PLS methods), our approach is more accurate, robust and reliable, and can be a potential excellent approach to quantify multicomponent with THz-TDS spectroscopy.